Morphology of antennal sensilla in doeringiella nobilis (Hymenoptera: Apidae) - Galvani, Gerónimo Luis (2008)
The distribution and morphology of antennal sensilla were investigated in females of Doeringiella (Triepeolus) nobilis (Friese) (Apidae, Epeolini) using scanning-electron microscopy. Sensilla campaniformia and three different types of sensilla trichodea were observed in the scape and pedicel. Sensilla trichodea and placodea were the most abundant types in all the flagellomeres. Variability in terms of length was observed in sensilla trichodea and to a lesser extent in sensilla basiconica, allowing further classification of these cuticular structures into types. Sensilla ampullacea, coeloconica and coelocapitula displayed a similar morphology to that reported for other hymenopterans. A previously unknown type of sensilla basiconica was observed in flagellomere nine.